ИХТИОФАУНА И ПЕРСПЕКТИВЫ РЫБОХОЗЯЙСТВЕННОГО ИСПОЛЬЗОВАНИЯ МАЛЫХ ГОРНЫХ ВОДОЕМОВ АЛАКОЛЬСКОГО РАЙОНА (НА ПРИМЕРЕ ВОДОХРАНИЛИЩА АБЖАНОВА И ОЗЕРА ЖАСЫЛКОЛЬ) (ҚазҰУ хабаршысы. Экология сериясы, 2016)
The fish fauna structure, the main biological indicators and productivity of young fishes in high-mountainous reservoirs of Alakol's region is resulted. The actions on fish economy using are recommended.